Multiplatform Mobile Robot as Robotics Technology Socialization Media - Ilham Akbar Darmawan, Nova Eka Budiyanta (International Journal of Advanced Science and Technology, 2020)
This study aims to develop a multiplatform robot that can be used as a medium to socialize robotics technology among adolescents. This multi-platform robot is also expected to help teens who are interested in robots to facilitate them in learning robotics technology. The robot made is a wheeled robot with manual control using a controller (manual transporter) and also automatic control using sensors (line follower and automatic avoider). The research methodology used in this study is the 4D development model (Define, Design, Develop, and Disseminate). Based on the test result, the robot runs accurately following the black or white lines and successfully moves items, for automatic avoiders the robot can detect walls and follow the grooves of the wall at an angle of 90 degrees, while for manual transporters the robot can be controlled using a controller application on an Android-based smartphone developed with MIT APP Inventor. In the dissemination stage, it is known that teenagers have a very high curiosity and desire, 86% and 90%. However, their interest and readiness to learn is not as high as their desire to master the robotics technology.